Projeto de letramento, argumentação e cidadania no contexto pandêmico: ler, escrever e agir nos anos iniciais do ensino fundamental - Oliveira, Stepheson Ray de (2023)
The Covid-19 pandemic has changed people's lives in many ways, impacting their actions in diverse areas of activities, especially those linked to education, requiring a reconfiguration of the running of the school. Among requirements to adaptation to this new type of teaching, schools and teachers implemented some innovative pedagogical practices and methodologies, mediated by technologies, due to the Emergency period, according to the Emergency Remote Teaching rules. Based on this problem, this research aims to investigate the way literacy projects can contribute to literacy and literacy processes focused on a citizen training of students in the early years of elementary school during Remote Emergency Teaching due to the pandemic of new coronavirus. Theoretically, this study has its base on the socialcultural literacy studies, which assume reading and writing as social practices; on the assumptions of the Bakhtin Circle, which propose the linguistic approach and the studies on discursive genres in the process of social interaction; besides on the contributions of the New Rhetoric, whose assumptions conceive the discursive genre as social action. Methodologically, this research has as base Applied Linguistics. Data collection was in 2021, in the Professor Severino Bezerra state school, in Tangará, Rio Grande do Norte, in a 5th grade class of the Elementary School. To analyze data, this research has a qualitative and interpretive approach. Preliminary results revealed an improvement of students' reading and writing training and a greater familiarity with argumentative genres, in addition to a greater mastery of technologies in school literacy practices. Since different practices during literacy training, students could write some argumentative texts in diverse genres (comments, opinion piece etc.), they took a position defending their opinions, with a more autonomous and critical attitude, that points the importance of literacy project to the critical education, which aims to train students to the effective exercise of citizenship.